2022
DOI: 10.31744/einstein_journal/2022rb6181
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of heat shock protein in abdominal organ transplantation?

Abstract: Ischemia-reperfusion injury is a pathophysiological event occuring after abdominal organ transplantation, and has a significant influence on prognosis and survival of the graft. It is involved in delaying the primary function or non-functioning of the graft. The objective of this study was to provide information on heat shock protein mechanisms in ischemia-reperfusion injuries in abdominal organ transplantations, and to indicate the possible factors involved that may influence the graft outcome. Several classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The same authors also showed that human lung recipients with moderate to severe CLAD had increased eATP concentration in bronchoalveolar lavage (BAL) fluid when compared to those without this injury [34]. In addition, eATP levels were increased in mouse lung allografts and become reduced when a nonselective inhibitor of purinergic receptors or a specific P2X7R inhibitor was applied and that was accompanied with diminished acute rejection and prolonged survival of mouse lung allografts [35].…”
Section: Discussionmentioning
confidence: 93%
“…The same authors also showed that human lung recipients with moderate to severe CLAD had increased eATP concentration in bronchoalveolar lavage (BAL) fluid when compared to those without this injury [34]. In addition, eATP levels were increased in mouse lung allografts and become reduced when a nonselective inhibitor of purinergic receptors or a specific P2X7R inhibitor was applied and that was accompanied with diminished acute rejection and prolonged survival of mouse lung allografts [35].…”
Section: Discussionmentioning
confidence: 93%
“…As for Hsp70, only its intracellular form was detected in lung allotransplantation. Its synthesis was stimulated by IRI, which is suggested to have a protective role on transplanted organs [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of HSPs has been found in numerous medical conditions, including autoimmune disorders, cardiovascular problems, skin conditions, and organ transplants [ 11 , 12 , 13 , 14 ]. Additionally, HSPs may play significant roles in the molecular mechanisms leading to cancer development and progression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%